Image Classification Based On Color Using Thresholding Method - Teguh Agara Selian; Niko Akbar; M. Irfan Hidayat (CV. Multimedia Teknologi Kreatif, 2025)
This research aims to categorize images based on color using the method of thresholding. Image classification based on color plays a crucial role in various applications such as object detection, traffic monitoring, and medical image processing. The thresholding method is a popular approach used in image segmentation due to its effectiveness and computational efficiency. In this method, grayscale images are converted into binary images by determining a specific threshold value. This research utilizes the thresholding method to separate pixels based on their color intensity. The research methodology consists of several steps, including dataset collection, image pre-processing, color feature extraction, application of the thresholding method, and class labeling. The study's benefits include object recognition, cost and time reduction in image classification, and improved product quality and income for farmers.